Decomposition of directed graphs and the Turán problem - Novikov, B.V.; Polyakova, L.Yu.; Zholtkevich, G.N. (Український математичний журнал, 2014)
We consider vertex decompositions of (di)graphs appearing in the automata theory and establish some properties of these decompositions. These decompositions are applied to the problem of forbidden subgraphs.